A Call for Universal Acceptance of the Milan System for Reporting Salivary Gland Cytopathology - Barbarite, Eric (Laryngoscope, 2019)
OBJECTIVES: The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) established a standardized, tiered reporting system for salivary gland fine-needle aspiration (FNA) that has gained international acceptance among cytologists. Our goal was to review the key features of the MSRSGC to familiarize the surgical community with this system and its application to the FNA evaluation of salivary gland masses. METHODS: A comprehensive review of the MSRSGC and its application in clinical practice. RESULTS: The MSRSGC consists of six major diagnostic categories: 1) nondiagnostic, 2) non-neoplastic, 3) atypia of undetermined significance, 4) neoplasm (benign or salivary gland neoplasm of uncertain malignant potential), 5) suspicious for malignancy, and 6) malignant. Each diagnostic category is associated with an implied risk of malignancy with implications for clinical management. CONCLUSIONS: The MSRSGC is similar to the system used for reporting thyroid FNA, which is familiar to most otolaryngologists and head and neck surgeons. As this reporting system continues to gain popularity among pathologists, widespread understanding by surgeons will be important to standardize communication and classification of salivary gland cytopathology to improve clinical care.